Microstrip Antenna with Photographic Paper Substrate for WLAN - D. S. Marotkar; P. L Zade (Institute of Advanced Engineering and Science, 2018)
In this paper a compact, flexible, Multiband antenna is designed. It is having flexible Substrate of photographic paper which makes the antenna conformal. The antenna with two U slots cut in radiating patch is offset fed by microstrip lines gives the multiple bands of WLAN /WIMAX Application and two parasitic Elements improves the bandwidth of a typical microstrip antenna. The Measured results shows that the antenna resonates between Frequency band 2.10-2.95 GHz, 3.35-3.54 GHz and 5.04-6.0Hz.which are used for application such as Bluetooth, Wi-Fi, Zigbee, ISM 2.4GHz,WLAN WiMAX, and WLAN 5.2GHz.